Perancangan Sistem Inventory Unit Logistik Bank Indonesia Bandung - Rijayana, Iwan; Tresti, Agnesia (Universitas Katolik Parahyangan, 2016)
In the era of information technology such as this present time efficiency and specialized as well as easy in getting any information it required institutions such as bank, always hold the inventory. In the absence of an inventory of institutions or companies at a time unable to meet its operational needs or activities.Design and implementation ofÂ planningÂ system in logistics unit inventory Bank Indonesia Bandung, is on such research produces a system application created using Vb.net and mean to solve a problem in the logistics unit of Bank Indonesia.As for the problem solving can assist the logistics unit to simplify Bank Indonesia Bandung logistics unit as unit of inventory suppliers to transact the expenditure items. Logging request items using a computerized system to make it more easily and stored into the database so that very small accurence of data loss.The result of this research are generating an application inventory system that serves to make a transaction request goods logistics unit as a provider goods supplies.